Odpowiedzi

2010-04-15T16:05:10+02:00
A) 1/2(4z+6)=3
4/2z + 6/2 = 3
2z + 3 = 3
2z = 3 - 3
2z = 0 /: 2
z = 0

b) -3(x-2)=-9
-3x + 6 = -9
-3x = -9 -6
-3x = -15 /: (-3)
x = 5

c) 2w+3=4w-5
2w - 4w = -5 - 3
-2w = -8 /: (-2)
w = 4

d) -t+2=4+5t
-t - 5t = 4 - 2
-6t = 2 /: (-6)
t = -2/6
t = -1/3
2010-04-15T16:07:45+02:00
A) 1/2(4z+6)=3
2z+3=3 / -3
2z=0 / :2
z=0
b) -3(x-2)=-9
-3x+6=39/-6
-3x=-15 / :(-3)
x=5
c) 2w+3=4w-5 / -4w
-2w+3=-5/-3
-2w=-8 / : (-2)
w=4
d) -t+2=4+5t /-5t
-6t+2=4 / -2
-6t=2 / :(-6)
t= - 2/6
t= -⅓

licze na naj !